2022
DOI: 10.1021/acsnano.2c02885
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Induced Isomeric Cu13 Nanoclusters: Chlorine to Copper Charge Transfer Boosting Molecular Oxygen Activation in Sulfide Selective Oxidation

Abstract: Isomers with minimal structural dissimilarities are promising research objects to obtain a comprehensive understanding of structure−property relationships; however, comparability of isomeric structures is a prerequisite. Herein, two quasi-structurally isomeric 13-nuclei copper nanoclusters (Cu NCs) (Cu13a and Cu13b) containing highly similar Cu 13 kernels and different arrangements of peripheral ligands were obtained using a solvent-induced strategy. The exotic chloride ion is shown to play a prominent role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 68 publications
0
51
0
Order By: Relevance
“…Sun et al have reported two quasi-structurally isomeric CuNCs of [Cu(I) 13 Na 2 (CZ-PrA) 6 (TC 4 A) 2 Cl(MeOH) 2 ] (CuNC-32a) and [Cu(I) 13 Na(CZ-PrA) 6 (TC 4 A) 2 (MeOH)]⋅ MeOH⋅DCM⋅CH 3 COCH 3 (CuNC-32b), where CZ-PrAH = 9-(prop-2-yn-1-yl)-9H-carbazole and H 4 TC4A = p-tertbutylthiacalix[4]arene, as shown in Figure 18A-a,b. [68] The Cu 13 kernel is built from a Cu 5 trigonal bipyramid sharing an equatorial Cu atom with a Cu 5 square pyramid, and the other two equatorial Cu atoms each is appended by two more Cu atoms (Figure 18A-c). In contrast, the Cu 5 trigonal bipyramid in CuNC-32a is more geometrically deformed due to a bridging Clion.…”
Section: Catalysis In Organic Synthesismentioning
confidence: 99%
“…Sun et al have reported two quasi-structurally isomeric CuNCs of [Cu(I) 13 Na 2 (CZ-PrA) 6 (TC 4 A) 2 Cl(MeOH) 2 ] (CuNC-32a) and [Cu(I) 13 Na(CZ-PrA) 6 (TC 4 A) 2 (MeOH)]⋅ MeOH⋅DCM⋅CH 3 COCH 3 (CuNC-32b), where CZ-PrAH = 9-(prop-2-yn-1-yl)-9H-carbazole and H 4 TC4A = p-tertbutylthiacalix[4]arene, as shown in Figure 18A-a,b. [68] The Cu 13 kernel is built from a Cu 5 trigonal bipyramid sharing an equatorial Cu atom with a Cu 5 square pyramid, and the other two equatorial Cu atoms each is appended by two more Cu atoms (Figure 18A-c). In contrast, the Cu 5 trigonal bipyramid in CuNC-32a is more geometrically deformed due to a bridging Clion.…”
Section: Catalysis In Organic Synthesismentioning
confidence: 99%
“…Compared to gold­(I) and silver­(I) clusters, copper­(I) clusters are more synthetically challenging because they are oxidation-sensitive. However, copper complexes are much cheaper than their congeners and always have good photophysical properties. The construction of copper­(I) clusters mainly includes two strategies: (i) applying copper­(I) precursors directly; , (ii) using comproportionation reactions by mixing copper­(II) salts with copper powders. Reductions of copper­(II) salts by reducing agents are also good alternatives for the preparation of copper­(I) clusters, which may allow for the serendipity of copper hydride clusters with diverse structures and applications in catalysis, hydrogen storage, and so on. The protecting ligands of copper hydride clusters include phosphines, alkynyls, dithiocarbamates, , dithiophosphates, thiols, selenols, and carbenes . Alkynyls have been demonstrated to be a kind of versatile ligand in the formation of coin-metal nanoclusters with diverse coordination modes. , However, only a few reports of copper hydride clusters involve alkynyls. ,, Mixed-ligand-protected metal clusters were reported to exhibit higher stability and enhanced properties compared to single-ligand-protected ones .…”
Section: Introductionmentioning
confidence: 99%
“…metal nanoclusters' crystal structures have been reported. Among them, structural units such as the 13-metal-atom icosahedron (M 13 ), [21][22][23] the 8-metal-atom cube (M 8 ), [24][25][26] and the 4-metal-atom tetrahedron (M 4 ) [27][28][29] are not only stable cluster forms, but also building blocks in hierarchically structured nanoclusters.…”
mentioning
confidence: 99%
“…Since the pioneering works on the structural determination of Au 102 (SC 6 H 4 COOH) 44 18 and Au 25 (SC 2 H 4 Ph) 18 , 19,20 hundreds of metal nanoclusters’ crystal structures have been reported. Among them, structural units such as the 13-metal-atom icosahedron (M 13 ), 21–23 the 8-metal-atom cube (M 8 ), 24–26 and the 4-metal-atom tetrahedron (M 4 ) 27–29 are not only stable cluster forms, but also building blocks in hierarchically structured nanoclusters.…”
mentioning
confidence: 99%